The Power of Place: The Irish West as a Case Study - Grgas-Mufa, Stipe (Array, 2008)
The article deals with the spatial practice whereby nations privilege certain locales in constructing and representing their identity. This strategy is illustrated by an analysis of the function of the west of Ireland both during the process of decolonisation and in the later period of state formation.